2019
DOI: 10.1155/2019/4780426
|View full text |Cite
|
Sign up to set email alerts
|

Short-Segment Instrumentation with Fractured Vertebrae Augmentation by Screws and Bone Substitute for Thoracolumbar Unstable Burst Fractures

Abstract: Background. For thoracolumbar burst fractures, traditional four-screw (one above and one below) short-segment instrumentation is popular and has a high failure rate. Additional augmentation at the fractured vertebrae is believed to reduce surgical failure. The purpose of this study was to examine the clinical and radiographic results of patients who underwent short-segment posterior instrumentation with augmentation by screws and bone substitutes at the fractured vertebrae and to compare these data to those of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…It was found that compared with OF4 and 5 types fractures, OF1-3 types fractures had better pain relief after PVP (23,24), which was consistent with the findings of our present study. Therefore, we speculated that for patients with severe vertebral fractures (such as complete burst fractures), the addition of bone cement-assisted fixation on the basis of internal fixation may achieve better pain relief (25). Surgical factors are important factors affecting the postoperative pain.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that compared with OF4 and 5 types fractures, OF1-3 types fractures had better pain relief after PVP (23,24), which was consistent with the findings of our present study. Therefore, we speculated that for patients with severe vertebral fractures (such as complete burst fractures), the addition of bone cement-assisted fixation on the basis of internal fixation may achieve better pain relief (25). Surgical factors are important factors affecting the postoperative pain.…”
Section: Discussionmentioning
confidence: 99%
“…Short-segment transpedicular screw fixation has been shown to achieve similar results in kyphosis correction and biomechanical stability maintenance to long-segment transpedicular screw fixation, and the screw placement of the fractured vertebra can better maintain the height of the fractured vertebra [ 19 ]. In addition, short-segment fixation can preserve more moving segments and reduce the incidence of adjacent segment degeneration [ 20 ]. Generally, the accepted standard treatment for thoracolumbar fractures with neurological deficit is decompression (anterior or posterior) with fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Posterior fixation is divided into single-segment fixation, short-segment fixation, and long-segment fixation. 7 Short-segment fixation is simple, less invasive, and more reliable. [8][9][10] However, since the anterior column of the thoracolumbar instability fracture is severely damaged, the use of short-segment fixation causes concentrated stress, thus easily resulting in failure of reduction and implant breakage, resulting in surgical failure.…”
Section: Neurospine Eissn 2586-6591 Pissn 2586-6583mentioning
confidence: 99%